Interaction between thyroid hormones and gonadotropin inhibitory hormone in ex vivo culture of zebrafish testis: An approach to study multifactorial control of spermatogenesis - Rodrigues, Maira S. [UNESP]; Fallah, Hamideh P.; Zanardini, Maya; Malafaia, Guilherme [UNESP]; Habibi, Hamid R.; Nóbrega, Rafael H. [UNESP] (Elsevier, 2021)
Reproduction is under multifactorial control of neurohormones, pituitary gonadotropins, as well as of local gonadal signaling systems including sex steroids, growth factors and non-coding RNAs. Among the factors, gonadotropin-inhibitory hormone (Gnih) is a novel RFamide neuropeptide which directly modulates gonadotropin synthesis and release from pituitary, and in the gonads, Gnih mediated inhibitory actions on gonadotropin response of zebrafish spermatogenesis. Thyroid hormones are peripheral hormones which are also known to interact with reproductive axis, in particular, regulating testicular development and function. This study investigated the interaction between Gnih and thyroid hormones in zebrafish spermatogenesis using in vivo and ex vivo approaches. Three experimental groups were established: “control” (non-treated fish), “methimazole” and “methimazole + T4”. Fish were exposed to goitrogen methimazole for 3 weeks; T4 (100 μg/L) was added in the water from the second week only in the “reversal treatment” group. After exposure, testes were dissected out and immediately incubated in Leibovitz's L-15 culture medium containing hCG, Gnih or hCG + Gnih for 7 days. Germ cell cysts and haploid cell population were evaluated by histomorphometry and flow cytometry, respectively. Our results showed that hypothyroidism affected germ cell development in basal and gonadotropin-induced spermatogenesis, in particular, meiosis and spermiogenesis. Hypothyroid testes showed lower amount of spermatozoa, and decreased potency of hCG. We also showed that goitrogen treatment nullified the inhibitory actions of Gnih on the gonadotropin-induced spermatogenesis. This study provided evidences that thyroid hormones are important regulatory factors for hCG- and Gnih-mediated functions in zebrafish spermatogenesis.
Keywords: Gnih; hCG; Hypothyroidism; Spermatogenesis; Thyroid hormones; Zebrafish